2016
DOI: 10.1021/acs.nanolett.6b01648
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Ultrasensitive Memristive Aptasensor

Abstract: We present the very first worldwide ever-reported electrochemical biosensor based on a memristive effect and DNA aptamers. This novel device is developed to propose a completely new approach in cancer diagnostics. In this study, an affinity-based technique is presented for the detection of the prostate specific antigen (PSA) using DNA aptamers. The hysteretic properties of memristive silicon nanowires functionalized with these DNA aptamers provide a label-free and ultrasensitive biodetection technique. The ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 23 publications
0
67
0
Order By: Relevance
“…[295][296][297][298][299] By considering metal-oxide NWs, in 2017 Zhang et al [178] exploited the resistive switching properties of ZnO NWs for the realization of gas sensors with high selectivity and improved recovery speed. Recently, it was shown that the memristive properties of suspended Si NWs realized by a top down approach can be strongly modulated by the presence of biomolecules, making possible the realization of highly sensitive biosensors.…”
Section: Memsensorsmentioning
confidence: 99%
“…[295][296][297][298][299] By considering metal-oxide NWs, in 2017 Zhang et al [178] exploited the resistive switching properties of ZnO NWs for the realization of gas sensors with high selectivity and improved recovery speed. Recently, it was shown that the memristive properties of suspended Si NWs realized by a top down approach can be strongly modulated by the presence of biomolecules, making possible the realization of highly sensitive biosensors.…”
Section: Memsensorsmentioning
confidence: 99%
“…Aptamers, for example, are small molecules with either nucleic acid or peptide structure that bind specific ligands, created by an in vitro affinity selection among a large amount of random sequences. [170] Due to their size advantage, there is an increasing interest on them in the FET community, as demonstrated by the large amount of ultrasensitive silicon nanowire-based aptasensors developed during the last years for detection of neuronal potassium ion efflux [57] (Figure 10b), dopamine [171] (Figure 10c), thrombin, [52] PSA, [172] and antivascular endothelial growth factor (VEGF) [173] among others. [170] Due to their size advantage, there is an increasing interest on them in the FET community, as demonstrated by the large amount of ultrasensitive silicon nanowire-based aptasensors developed during the last years for detection of neuronal potassium ion efflux [57] (Figure 10b), dopamine [171] (Figure 10c), thrombin, [52] PSA, [172] and antivascular endothelial growth factor (VEGF) [173] among others.…”
Section: Small Receptorsmentioning
confidence: 99%
“…Graph shows the real-time measurement where stimulation with α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) is followed by K + efflux, while 6,7-dinitroquinoxaline-2,3-dione (DNQX) blocking brings the absence of response upon repeated AMPA stimulation. [172] However, measuring in dry can be irregular, unstable, and with higher variations than measuring directly in a liquid sample using controlled potentials via reference electrode. [57] Copyright 2017, ACS Publications.…”
Section: Alternative Measurement Modesmentioning
confidence: 99%
See 2 more Smart Citations